Vitamin D insufficiency among Indian athletes and its association with CYP2R1 (rs10741657) polymorphism - Manjappa, K.; Cherian, K.; Kotturu, S.; Durgam, D.; Ghosh, S.; Yagnambhat, V. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Vitamin D insufficiency negatively impacts the health and training efficiency of athletes. The growing prevalence of vitamin D deficiency worldwide might be a combined outcome of dietary inadequacy, less exposure to sun, and genetic predisposition. Variations in CYP2R1 gene have been linked by several studies to vitamin D serum concentration. Especially, the rs10741657(G) allele has been associated with lower vitamin D status and thus a potential cause for Vitamin D insufficiency. Although more than 76% of Indians suffer from vitamin D deficiency, currently there are no studies on Vitamin D levels in Indian Athletes and understanding the genetic predisposition to lower vitamin D status. Thus, the aim of this study was to check for an association between CYP2R1 polymorphism and Vitamin D levels of athletes participating across different sporting category.